Can Sonographic Fetal Biometry Predict Adverse Perinatal Outcome? - Pretscher, Jutta; Schwenke, Eva; Baier, Friederike; Kehl, Sven; Schneider, Michael; Stumpfe, Florian Matthias; Schmid, Matthias; Beckmann, Matthias; Mayr, Andreas; Schild, Ralf; Faschingbauer, Florian (Ultraschall in der Medizin, 2019)
Objective To evaluate the association of sonographic fetal biometry (sonographic head circumference (soHC), sonographic abdominal circumference (soAC), estimated fetal weight (EFW)) with mode of delivery and adverse perinatal outcome. Methods Singleton pregnancies with a gestational age ≥ 37 weeks and an ultrasound examination with complete biometric parameters within 7 days before delivery were retrospectively included. The association between soHC, soAC, EFW and fetal (5-min Apgar < 7, pH < 7.1, neonatal intensive care unit (NICU) admission, shoulder dystocia (ShD)) and maternal (obstetric intervention (OI): caesarean or vaginal operative delivery, obstetric anal sphincter injury syndrome (OASIS), postpartum hemorrhage (pph)) adverse outcomes were analyzed using univariate and multivariate logistic regression analyses. Results 12 396 women were included and 3479 (28.07 %) needed an OI. Multivariate analyses demonstrated significant contributions for the prediction of OI by soHC and soAC, whereas EFW did not reach significance. The highest OR was shown for soHC (1087, p < 0.001). ShD occurred in 73 (0.59 %) of the deliveries. Multivariate analyses showed that significant contributions for the prediction of ShD were provided only by soAC (OR 1460, p = 0.007). For the other maternal and neonatal adverse outcome parameters, no significant association with the biometric measurements could be demonstrated in the multivariate analyses. The overall detection rates for the prediction of adverse perinatal outcome by the different biometric parameters and EFW were poor. Conclusion Obstetric management decisions should not be based solely on measurements of biometric parameters or EFW.
CRIS-Team Scopus Importer:2019-05-02
Keywords: adverse perinatal outcome; biometric parameters; fetal weight estimation; mode of delivery; ultrasound